Anthropometric and physical fitness norms for students from Governador Celso Ramos (SC), ages 11 to 14 - Madureira, Alberto Saturno (Journal of Physical Education (Maringá), 2008)
The purpose of this study was to collect anthropometric and helth-related physical fitness data of students from state schools in Governador Celso Ramos, SC., ages 11 to 14. A second purpose was to develop anthropometric and helth-related physical fitness norms for the population under investigation. A number of 283 out of 371 students regularly attendeing classes were measured. Anthropometric measurements included weight (Kg) and height (cm). Helth-related physical fitness was evaluated through the AAHPERD Test (1980, which included measurements of: a) triceps and subscapular skinfolds (body composition), b) one-minute sit-up and sit-and-reach test (musculoskeletal function), 9-minute run walk test (cardiorespiratory endurance). The collection of the data was done in two weeks, during the mornings and afternoons. Statistical analysis and the development of percentil norms was done utilizing the SAS programs (IBM computer). The level of significance was set at 0.05. Results from this study have shown that: a) Except for the 14 year old group, girls were taller than boys; b) Skinfold measures were higher in girls for all age groups; c) Flexibility values were higher for girls, but, it was statistically significant only for the 14-year old group; d) Boy had better values for the abdominal test in all age groups (p < 0.05); the same happened for the 9-minute (11 and years of age) and the 12-minute run/walk test (13 and 14 years of age). Norms were developed for each age group and sex. Despite the limitations present in this investigation, it is believed that the norms may be utilized by teachers from the surrounding areas nearby the City of governador Celso Ramos, SC. Norms should be reviewd in three to five years from now.